2018
DOI: 10.3389/feduc.2018.00013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Entrepreneurship Training on Entrepreneurial Efficacy and Alertness among Adolescent Youth

Abstract: Our study focuses on the impact of systematic entrepreneurship training comprising both active and passive learning activities on entrepreneurial alertness and efficacy among adolescent youth. Reports from a two-wave online survey among 328 students from five secondary schools (aged 13-16 years; 34.8% male and 65.2% female) reveal that those who went through entrepreneurship training (treatment group, N = 142) had significantly higher entrepreneurial alertness and efficacy levels compared to those who did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 57 publications
4
58
0
4
Order By: Relevance
“…Entrepreneurship education is an approach to learning that has been adopted across Asia, in China, Indonesia, , Singapore (Ho et al, 2018) and Malaysia (Din et al, 2016), in most of the European Union countries, and in the United States, with the European Union countries taking a more practical approach (Ierapetritis, 2017). Global interest grew on the topic of entrepreneurship in the early 1980s as the economy's focus turned to small and medium-sized (SME) businesses as a solution to unemployment (Jones & Iredale, 2014;Pepin, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship education is an approach to learning that has been adopted across Asia, in China, Indonesia, , Singapore (Ho et al, 2018) and Malaysia (Din et al, 2016), in most of the European Union countries, and in the United States, with the European Union countries taking a more practical approach (Ierapetritis, 2017). Global interest grew on the topic of entrepreneurship in the early 1980s as the economy's focus turned to small and medium-sized (SME) businesses as a solution to unemployment (Jones & Iredale, 2014;Pepin, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Positive attitude, subjective norm, image, finances and perceived behavioural control were found to increase intent. Ho et al (2018) used the theory and found positive levels of engagement in 836 secondary school students when using venture creation in Singapore.…”
Section: Developing Entrepreneurial Intentmentioning
confidence: 99%
“…In line with the Social Cognitive Career Theory (Hackett and Lent, 1992;Lent and Brown, 2013), entrepreneurial self-efficacy develops from entrepreneurial socialization or learning occurring through education, training, and experiences that enhance the skills and mastery experiences of novice entrepreneurs. In a number of studies, individuals who have undertaken entrepreneurial training formally or informally have reported higher levels of entrepreneurial self-efficacy (Ho et al, 2018;St-Jean and Tremblay, 2020). However, this may be dependent on the protégés' learning orientation (St-Jean et al, 2018).…”
Section: The Role Of Self-efficacymentioning
confidence: 99%
“…There are multiple learning approaches that can offer students opportunities to explore the development of skills required of a musician in today's context. Examples of these learning approaches include 'Enterprise Pedagogy' (Garnett, 2013) and Entrepreneurial Learning (Ringo -Ho, et al, 2018).…”
Section: Positioning Pedagogy That Caters For Music Pathwaysmentioning
confidence: 99%